Combining radiomics and deep learning to predict liver metastasis of gastric cancer on CT image - Guo, Yimin; Yin, Haixiang; Zhang, Hanyue; Liang, Pan; Gao, Jianbo; Cheng, Ming (Frontiers in Oncology, 2025)
ObjectiveOur study aimed to explore the potential of deep learning (DL) radiomics features from CT images of primary gastric cancer (GC) in predicting gastric cancer liver metastasis (GCLM) by establishing and verifying a prediction model based on clinical factors, classical radiomics and DL features.MethodsWe retrospectively analyzed 1001 pathologically confirmed GC patients from June 2014 to May 2024, divided into non-LM (n=689) and LM groups (n=312). CT-based classic radiomics and DL features were extracted and screened to construct a DL-radiomics score. This score, along with statistically significant clinical factors, was used to build a fused model which visualized as a nomogram. The model’s predictive performance, calibration, and clinical utility were assessed and compared against a clinical model. Additionally, the DL-radiomics score’s role in distinguishing between synchronous and metachronous GCLM was evaluated.ResultsThe fused model showed good predictive performance [AUC: 0.796 (95% CI: 0.766-0.826) in training cohort and 0.787 (95% CI: 0.741-0.834) in test cohort], outperforming the clinical model, radiomics score and DL score (P<0.05). In addition, the decision curve confirmed that the model provided the largest clinical net benefit compared with all other models in the relevant threshold. DL-radiomics score showed moderate predictive performance in distinguishing between synchronous GCLM and metachronous GCLM, with an AUC of 0.665 (95% CI, 0.613-0.718).ConclusionThe CT-based fused model has demonstrated significant value in predicting the occurrence of GCLM, and can provide a reference for the personalized follow-up and treatment of patients.